Evaluation of larvicidal potential of β-sitosterol isolated from indigenous Aegle marmelos Correa crude leaf extracts against blood feeding parasites and its binding affinity studies towards sterol carrier protein. (October 2018) - Angajala, Gangadhara; Subashini, Radhakrishnan
Abstract: Mosquito transmitted diseases represent a significant threat to human life all over the world for decades. The secondary metabolites obtained from plants may serve as excellent alternative sources for parasitic control in the near future as they possess various potent bioactive compounds which act as effective mosquito controlling agents and moreover they are nontoxic and easily biodegradable. In the present study β-sitosterol was isolated from the crude aqueous leaf extracts of indigenous Aegle marmelos Correa and characterized by using FT-IR (Fourier Transform Infrared) spectroscopy, 1 H NMR (Nuclear Magnetic Resonance), 13 C NMR, DEPT (Distortionless enhancement by polarization transfer) and GC-MS (Gas Chromatography-Mass Spectroscopy) techniques. The isolated compound and crude leaf extracts were evaluated and compared for its larvicidal efficacy. Results showed that the isolated β-sitosterol possess significant mortality rate against A.aegypti and C.quinquefasciatus (LC50 480.19 and 450.19 ppm) respectively. From the computationally predicted molecular docking analysis it was found that β-sitosterol is having stronger binding interaction (−6.8 kcal/mole) with the SCP-2 receptor which was comparable to standard Temephos (−7.3 kcal/mole). Graphical abstract: Highlights: β-sitosterol from the crude aqueous leaf extracts of indigenous Aegle marmelos Correa . Characterization of β-sitosterol using FT-IR, 1 H NMR, 13 C NMR, DEPT and GC-MS. Good larvicidal efficacy against the early third instar larvae of Aedes aegypti and Culex quinquefaciatus. Binding affinity of β-sitosterol towards SCP-2 protein was comparable to Temephos.